Understanding activation and growth of twin variants in polycrystalline magnesium under tension and compression: An atomistic study - Huicong Chen; Cheng Chen; Jun Song; Stephen Yue (Journal of Magnesium and Alloys)
Deformation twinning is known to be important in the acquisition of plasticity for hexagonal close-packed crystal structures, of great implication to the design and development of novel high-strength Mg alloys with enhanced formability. Accurate understanding of deformation twinning necessitates critical mechanistic knowledge of the activation and selection of twins at nanoscale. In this work, considering polycrystalline Mg, we performed comprehensive molecular dynamics simulations to investigate deformation twinning under uniaxial tension and compression loading. An algorithm has been developed and implemented to identify the active twin variants of three operating twin modes during deformation. Sharp contrast between tension and compression loading in terms of twin patterns and twin growth was observed, attributed to difference in twin variant activation and twin-twin interaction under the two loading conditions. Furthermore, the critical role of Schmid factor in twin variant activation and selection has been elucidated, in good agreement with experimental observations. This study contributes critical insights towards advancing our understanding of the complex behaviors of deformation twinning in polycrystalline Mg.